1968
DOI: 10.1128/jb.95.2.350-354.1968
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Dependence of Monosaccharide Transport in Nocardia

Abstract: Uptake of the monosaccharides D-glucose and D-mannose by Nocardia asteroides and N. brasiliensis is dependent on the presence of an adequate phosphate concentration in the environment. When phosphate is replaced by solutions of sodium chloride or potassium chloride of identical ionic strength, there is no sugar uptake. In the presence of iso-osmolar concentrations of sodium arsenate, there is, however, sugar uptake activation. When nonmetabolizable 3-0-methyl D-glucose is used, most of the sugar taken up can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1969
1969
1975
1975

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In addition, they concluded that glycerol uptake was by facilitated diffusion or active transport at concentrations of glycerol below 80 ,uM, and by "free diffusion" at higher glycerol concentrations. Cerbon and Ortigoza-Perado (3) observed that in N. asteroides and N. brasiliensis the uptake of D-glucose and D-mannose was dependent upon an optimal supply of exogenous phosphate. They also demonstrated that D-glucose was taken up by facilitated diffusion.…”
mentioning
confidence: 98%
“…In addition, they concluded that glycerol uptake was by facilitated diffusion or active transport at concentrations of glycerol below 80 ,uM, and by "free diffusion" at higher glycerol concentrations. Cerbon and Ortigoza-Perado (3) observed that in N. asteroides and N. brasiliensis the uptake of D-glucose and D-mannose was dependent upon an optimal supply of exogenous phosphate. They also demonstrated that D-glucose was taken up by facilitated diffusion.…”
mentioning
confidence: 98%
“…There is evidence for mutual cross-resistance between arsenite and arsenate in Pseudomonas pseudomallei (1). Neither proteins, ribonucleic acid, nor deoxyribonucleic acid could be shown to be the receptors for arsenite in P. pseudomallei (1), and arsenate can replace phosphate in the monosaccharide transport system of Nocardia which is completely dependent on this anion (4). It is also known that the lipid extract of this microorganism contains most of the bound arsenic (5).…”
mentioning
confidence: 99%